Pengaruh Metode Cooperative Script terhadap Prestasi Belajar Siswa Kelas III pada Mata Pelajaran Fiqih di Pondok Pesantren Raudhatussalam Yogyakarta: The Effect of Cooperative Script Method On Learning Achievement of 3rd Grade Students On Fiqh Subject In Raudhatussalam Islamic Boarding School Yogyakarta - Zulfa Azka Azkia; Defi Firmansah; Irfan Nusantara Putra (Educan, 2024)
Applying the learning method can create active students in the learning process. One of them is the Cooperative Script Method, where the students are invited to play an active role in delivering learning material, and then at the end of the implementation, the teacher draws conclusions and makes clear explanations about the material. Fiqh is the chosen lesson because it discusses various laws from several Islamic teachings. From the step in this method, it can invite children to read, understand the lesson, and explain what they have understood to their classmates. And then, they understand better and can distinguish between one law and another. This study aimed to determine the effect of this method on the learning achievement of 3rd-grade students in Fiqh lesson at Raudhatussalam Islamic Boarding School. The research used a quantitative method, and the research design was a True Experiment with the post-test Control Group Design. This study took a sample of result from all student of 3rd grade student totaling 31 with 15 people being the control class and 16 people being the experimental class. The data analysis technique is used in descriptive analysis, prerequisite tests, and hypothesis testing with Mann Whitney. The result showed that sig. 0,01 < 0,05. It shows the influence of applying the Cooperative Script Method on learning achievement of 3rd-grade students in Fiqh lesson at Raudhatussalam Islamic Boarding School.